Pelatihan Keterampilan Berbicara Bahasa Indonesia bagi Mahasiswa dari Thailand di Universitas Muhammadiyah Palangkaraya - Dwi Sari Usop; Lastaria Lastaria; Arif Supriyadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Indonesian speaking skills is essential for foreign students from Thailand who was educated in Indonesia, especially at Muhammadiyah University of Palangkaraya. Through skills for speaking Indonesian properly, Thai students were able to communicate with people residing in the vicinity. Particularly, in understanding the course material and expression. Indonesian language course for speaking skill for Thai students in Muhammadiyah University of Palangkaraya aims to make the students able to recognize and understand the diversity of Indonesian and serves as a science to improve impaired speech in the Indonesian language, which will also affect the ability to write Indonesian. Through course, Muhammadiyah University of Palangkaraya students’ who came from Thailand has been quite able to recite the alphabet and make a simple sentence that can be used in communications. However, this ability stills needs to be aharpened in order to become proficient communicate using Indonesian.